OVERLAPPING PONTINE SYNDROME SYMPTOMATOLOGY: A RUPTURED CEREBELLAR PEDUNCLE ARTERIOVENOUS MALFORMATION - Abrar, Muhammad Nabil; Danishara, Mahawikan Akmal; Putra, Gabriel Zefanya Handoko; Addimaysqi, Rafi; Adrianto, Yudhi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Localizing brainstem lesions depends on identifying specific clinical syndromes. In the pons, the commonly confused Millard-Gubler and Foville syndromes share similar features. Millard-Gubler syndrome arises from a ventral pontine lesion, causing ipsilateral CN VII and CN VI palsies with contralateral hemiparesis while preserving conjugate gaze. In contrast, Foville syndrome involves a dorsal pontine lesion and is distinguished by ipsilateral conjugate gaze palsy due to pontine gaze center involvement. Case Report: This case describes a 56-year-old female patient with neurological deficits of crossed hemiparesis manifested by left-sided hemiparesis, hemihypesthesia and right-sided lower motor facial palsy, pathognomonic for a brainstem syndrome. Computed tomographic angiography (CTA) imaging revealed a cerebellar peduncle arteriovenous malformation (AVM) rupture with an intranidal aneurysm related to the brainstem syndrome. The anatomical lesion and clinical manifestations are considerably consistent with the definitions of Millard-Gubler and Foville syndrome. Upon DSA, the intranidal aneurysm was spontaneously thrombosed, leading to a decision to leave the AVM without intervention. Discussion: The clinical manifestations of ventrocaudal pontine lesions include Millard-Gubler and Foville syndromes. In this patient, involvement of the ventrocaudal and dorsomedial pons affected the abducens nucleus, facial colliculus, and corticospinal tract, producing overlapping Millard-Gubler and Foville features. Unlike typical ischemic or hemorrhagic pontine syndromes, this presentation resulted from secondary pontine hemorrhage due to a ruptured cerebellar peduncle AVM. Spontaneous thrombosis of the AVM nidus further created a therapeutic dilemma given its poorly defined natural history. Conclusion: This case illustrates that classic brainstem syndromes may arise from rare structural causes such as AVMs and highlights spontaneous thrombosis as a rare event complicating management. Recognition of atypical etiologies and the use of comprehensive neuroimaging are essential for accurate diagnosis and identification of potentially treatable vascular lesions.